Sovereign bond spreads and credit sensitivity - Ricardo Schefer (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2020)
Expectations of risky bond payments are unobservable and recovery rates for sovereigns are hard to estimate because they have no contractual claims to defined assets and samples of defaults are limited. A geometric version of credit spread is used to derive expected payments, dependent on idiosyncratic risk and unrelated to interest rates. The expectations are used to define a measure of price sensitivity to credit risk perceptions, or credit duration, improving the ambiguity of modified yield duration.
Keywords: D84; F34; G12; H63; 330; bond; sovereign; spread; expected; risk neutral; default; duration; yield